THE CHARACTER OF SOCIAL CARE IN CITIZENSHIP EDUCATION (PKn) LEARNING IN ELEMENTARY SCHOOLS - Hermansyah, Yus; Nurishlah, Laesti; Nurul Syahidah, Raihana (Universitas Efarina, 2021)
This research is motivated by the problem of student character which is a challenge for every Civics teacher to be able to direct the character of students who were previously not good into students who have good character. Environmental conditions in real life have found the behavior of many citizens who are not yet aware of environmental preservation to support their survival. The aim of this research is to determine the character of social care in citizenship education (PKn) learning in elementary schools. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of this research show that the character of caring for the environment can be formed in students through a Citizenship Education learning model that is interesting and familiar to students. It is time for students to learn directly and interact in a real way in the living environment which is their learning environment. Students who carry out comfortable learning activities will influence the success of learning at school.